The Influence of Principal’s Leadership and Principal’s Supervision on Teacher’s Performance - Putra, Dwi Sucipto Mandala; Arafat, Yasir; Ahyani, Nur (Yayasan Sembilan Pemuda Indonesia, 2024)
The study reveals that there is a noteworthy correlation between the supervision and leadership of school principals and teacher performance. Would the outcomes of this study, however, alter or remain the same if it had been carried out at a different location and time from earlier research? As a result, in contrast to earlier studies, this one will examine the effects of principle supervision and leadership concurrently but in a different setting. The purpose of the study is to ascertain and evaluate if the leadership and supervision of the school principal have an impact on the performance of teachers. The Export Facto approach is utilized in quantitative research. There are 25 study trials out of 75 populations, with a sample of 50 teachers. Data collecting approaches include questionnaires, paperwork, and interviews to get research data. This study found that principal supervision (X2) and leadership (X1) together had a substantial impact on teacher performance (Y) of 56.7%.